Philippine medical thesaurus on anatomy musculoskeletal system in Bicolano - De los Santos, Maricar S.; Tarlit, Rodolfo Y. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2004)
The Multilingual Philippine Medical thesaurus is part of a collaborative effort of the Institute of Library and Information Science, University of the Philippines Diliman, and the College of Medicine, University of the Philippines, Manila. Its main purpose is to come up with a tool for enhanced medical informatics research in the Philippines to aid the Filipino users and therefore lessen the difficulty and misconceptions in medical terminologies employed in the Philippines.
Philippine Medical Thesaurs on Anatomy: Musculoskeletal System in Bicolano is one of the many thesauri included in the Multilingual Philippine Medical Thesaurus project as mentioned above.
Bicolano was chosen as the language in which the medical terms were translated since the researcher's clan come from Bicol, the region that dominates the southernmost peninsula of the island of Luzon and extends into the island provinces of Catanduanes and Masbate. Bicolano is classified as a Central Philippine language, which is a sub-branch of the Meso Philippine-Western-Malayo Polynesian languages.
Just to emphasize, the researcher did not cover all the dialects spoken in the said region. For the reader's information, the Bicolano language differs according to location. Standard Bicolano language, as it approaches Tagalog-speaking areas tends to become quite similar to Visayan language. Accordingly, standard Bicolano language is usually attributed to the traditional cultural center of Naga City and its immediate environs. In this connection, the researcher focused on the language spoken in Naga City and areas near it. And to clarify the terms gathered, the researcher relied on the ranked translation tools by two experts in Bicolano dictionaries. They are Dr. Jesus Ramos of the University of the Philippines Departamento ng Filipino at Panitikan ng Pilipinas and Prof. Jesus Federico Hernandez of www.linguistics.com for accuracy purposes. Terms were gathered from the Medical subject Headings, 2004. Out of the one-hundred seventy-two (172) terms gathered, only sixty-six (66) terms have equivalent Bicolano terms. Therefore, one-hundred six (106) terms do not have their equivalent in Bicolano.
This study provided only the hierarchical and associative relationships of terms using such symbols as BT for Broader term, NT for Narrower term, and RT for Related term. Related terms were taken from the MeSH Descriptor Data designated as See Also. Scope noted (SN) were also included to explain the meaning of the translated terms. These were provided by the respondents. These notes were also written in Bicolano. Only one side of the equivalent relationship of terms is provided, i.e., Used For (UF) inasmuch as its reciprocal, Use, was completely generated in another set of research.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Subject headings, Bicolano -- Medicine; Subject headings, Bicolano -- Musculoskeletal system; Bicolano language -- Medical Bicolano